Charlotte's bones : the Beluga whale in a farmer's field - Rounds, Erin; Carver, Alison (Illustrator) (Thomaston, Maine : Tilbury House Publishers, 2018)
Many thousand of years ago, when a sheet of ice up to a mile thick began to let go of the land, the Atlantic Ocean flooded great valleys that had been scooped out by glaciers, and the salty waves of an inland sea lapped the green hills of Vermont. Into this arm of the sea swam Charlotte.
Includes bibliographical references.
940L
Keywords: White whale -- Juvenile literature; Glaciers -- Juvenile literature; Pleistocene-Holocene boundary; Geology, Stratigraphic -- Holocene -- Juvenile literature; Life cycles (Biology) -- Juvenile literature